HUBUNGAN FREKUENSI KONSUMSI MAKANAN JAJANAN DENGAN STATUS GIZI DAN PRESTASI BELAJAR ANAK SEKOLAH DASAR NEGERI MALALAYANG KOTA MANADO - Nasrudin Nasrudin; Fred A. Rumagit; Meildy E. Pascoal (POLTEKKES KEMENKES MANADO, 2016)
Learning achievement is the result of learning activities, which explain student’s mastered inthe material that given by the teachers. Learning achievement can be influence by personalnutrition status. Ideal nutrition status or optimal nutrition status occurs when human bodyobtain substances nutrients from food that used efficiently, enabling the physical growth,brain growth, work ability and healthy in general at the possible highest level. One of them issnack food which given contribute to the person’s energy. This experiment aimed to knowthe correlation of the Frequency Consumption of Snack Food with Nutrition Status andStudents’ Achievement in Malalayang Elementary School.This kind of research is observational analytic with cross sectional study, which started toimplemented at 1 March until 8 March in Elementary School Malalayang, Manado city withusing 77 samples. The samples taken with the age criteria 8-12 years old, in healthycondition, ever consumed snack food and willing to become respondents. Data analysisstarted with normality sample test and unvaried interpretation and bivariate analysis.There are 96,1% children’s that had good report values, frequency consumed snack foodwith categories often 72.7%, and normal nutrition status 71,4%. There is relationshipbetween the frequency of snack food consumption with nutrition status p=0.012, a=0.05.There is no statistical relationship between nutrition status and learning achievementp=1.00, a=0.05. Suggested that parents and teachers can monitor and provide nutritioneducation for children to choose healthy snack food to avoid healthy nutrition problems andothers health.